1997
DOI: 10.1080/0156655970440403
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Self‐Determination and Implications for Educational Interventions with Students with Disabilities

Abstract: Self-determination is, increasingly, recognised as an important educational outcome if students with disabilities are to succeed both in and out of school. This article presents a definitional framework of self-determination, describes the development of this outcome, and discusses the implications of this research for educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 56 publications
0
50
0
1
Order By: Relevance
“…Fifth, the next generation of research and development efforts on self-determination instructional and curricular intervention packages might target its work on transitional outcomes-that is, outcomes associated with the four domains identified by Wehmeyer, Sands, Doll, and Palmer (1997) of behavioral autonomy, self-regulation, psychological empowerment, and self-realization, and not academic outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Fifth, the next generation of research and development efforts on self-determination instructional and curricular intervention packages might target its work on transitional outcomes-that is, outcomes associated with the four domains identified by Wehmeyer, Sands, Doll, and Palmer (1997) of behavioral autonomy, self-regulation, psychological empowerment, and self-realization, and not academic outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, pupils are not invited to use nor develop their cognitive or motivational self-regulatory skills, but are still mostly expected to reproduce and apply the new information that the teacher has presented or made available (Boekaerts, 1997). Although research results in this field indicated the importance to adjust teaching environments in order to promote self-regulated learning (Palmer & Wehmeyer, 2003;Perry, 1998;Wehmeyer & Palmer, 2000;Wehmeyer, Sands, Doll, & Palmer, 1997;Willoughby, Porter, Belsito, & Yearsley, 1999), little is known about the extent to which primary school teachers embrace the concept of self-regulated learning and if teachers consider it as suitable for primary school practice. Gaining insight in how primary school teachers think about an innovation such as self-regulated learning for primary school practice could provide valuable information in explaining the occurrence or absence of such SRL practices.…”
Section: Self-regulated Learning In Primary Schoolmentioning
confidence: 99%
“…The actions of selfdetermined people enable them to fulfill roles typically associated with adulthood (Wehmeyer, Sands, Doll, & Palmer, 1997). Self-determination emerges across the life span as children and adolescents learn skills and develop attitudes which enable them to become causal agents of their own lives.…”
Section: Definitions Of Self-determinationmentioning
confidence: 99%